Wettability of thermoplastic and thermoset polymers with carbon nanotube grafted carbon fiber. (2021) - Bedi, Harpreet Singh; Kumar, Sunil; Agnihotri, Prabhat K.
Abstract: In this experimental study the wetting behavior of unsized and carbon nanotube (CNT) grafted carbon fibers is assessed with various polymers. Thermoset epoxy and two thermoplastics (polypropylene and polycarbonate) are tested. Sessile drop method and drop-on-fiber method are employed to quantify the wettability of various fiber/polymer combinations. Contact angle measurements based on the above two methods give insights into the effectiveness of various polymers to wet different types of carbon fiber fabrics and single fiber filaments. Moreover, the effect of CNT length and density on the wettability of carbon fibers is ascertained by synthesizing nanotubes on the fiber surface for varying time durations (10–30 min). CNT grafting reduces the contact angle of the polymer drop with carbon fiber; however, too much growth of nanotubes on the fiber surface leads to improper impregnation of the polymer into the carbon fabric. While polypropylene shows better wetting characteristics with unsized and CNT grafted carbon fibers, polycarbonate shows poor wettability.